Alleviation of Al Toxicity by Si Is Associated with the Formation of Al–Si Complexes in Root Tissues of Sorghum - Kopittke, Peter M.; Gianoncelli, Alessandra; Kourousias, George; Green, Kathryn; McKenna, Brigid A. (Frontiers in Plant Science, 2017)
Silicon is reported to reduce the toxic effects of Al on root elongation but the in planta mechanism by which this occurs remains unclear. Using seedlings of soybean (Glycine max) and sorghum (Sorghum bicolor), we examined the effect of up to 2 mM Si on root elongation rate (RER) in Al-toxic nutrient solutions. Synchrotron-based low energy X-ray fluorescence (LEXRF) was then used for the in situ examination of the distribution of Al and Si within cross-sections cut from the apical tissues of sorghum roots. The addition of Si potentially increased RER in Al-toxic solutions, with RER being up to ca. 0.3 mm h 1 (14 %) higher for soybean and ca. 0.2 mm h 1 (17 %) higher for sorghum relative to solutions without added Si. This improvement in RER could not be attributed to a change in Al-chemistry of the bulk nutrient solution, nor was it due to a change in the concentration of Al within the apical (0-10 mm) root tissues. Using LEXRF to examine sorghum, it was demonstrated that in roots exposed to both Al and Si, much of the Al was co-located with Si in the mucigel and outer apoplast. These observations suggest that Si reduces the toxicity of Al in planta through formation of Al-Si complexes in mucigel and outer cellular tissues, thereby decreasing the binding of Al to the cell wall where it is known to inhibit wall loosening as required for cell elongation.